Predictive Maintenance in Smart Grids with Long Short-Term Memory Networks (LSTM) - Goyal, Himanshu Rai; Almusawi, Muntather; Otero-Potosi, Santiago; Varshney, Neeraj; Sharma, Vishal; Rao, A Kakoli (2024 International Conference on Communication, Computer Sciences and Engineering (IC3SE), 2024)
This research explores the application of Long Short-Term Memory Systems (LSTMs) and conventional machine learning calculations for prescient support in shrewd grids. Leveraging a differing dataset, the study compares the execution of these models, uncovering that the LSTM demonstration outperforms conventional partners such as Random Forest, Support Vector Machine, as well as K-Nearest Neighbors. The LSTM's capacity to capture intricate worldly conditions in successive information contributes to its predominant precision, precision, recall, and F1 score in anticipating hardware disappointments and support needs. Comparative examinations highlight the transformative potential of LSTM systems in improving the unwavering quality and proficiency of prescient support in energetic keen framework situations. The study adjusts with current patterns in related writing, emphasizing the developing noticeable quality of profound learning procedures in tending to complex assignments inside the vitality segment. As savvy grids advance, joining progressed data-driven approaches gets to be basic, and this investigation underscores the urgent part of LSTMs in handling the challenges related to prescient maintenance. The discoveries not as it were contribute to the body of information within the field but also offer practical suggestions for the improvement of clever and flexible smart network frameworks.